2018
DOI: 10.1088/1755-1315/102/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Field efficacy of entomopathogenic fungiBeauveria bassiana(Balsamo.) for the management of mungbean insect pests

Abstract: Abstract. In order to reduce the use of insecticide, the application of Beauveria bassiana may be an alternative control. The objective of this study was to evaluate the efficacy of B. bassiana for controlling mungbean pest. The experiment was conducted in Ngale Research Station from February to May 2017, using randomized block design, seven treatments, four replicates. The treatments were frequency of application; P1= six times, P2= five times, P3= four times, P4= three times, P5= once, P6= full protection us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Vuill. is an important natural pathogen of insects and it has been developed as a microbial insecticide for use against many major arthropod pests in agricultural, urban, forest, livestock and aquatic environments (Charnley and Collins, 2007, and Bayu and Prayogo, 2018, María ,et al 2019. It has been developed as a microbial insecticide for use against many major pests, including lepidopterans and orthopterans.…”
Section: Introductionmentioning
confidence: 99%
“…Vuill. is an important natural pathogen of insects and it has been developed as a microbial insecticide for use against many major arthropod pests in agricultural, urban, forest, livestock and aquatic environments (Charnley and Collins, 2007, and Bayu and Prayogo, 2018, María ,et al 2019. It has been developed as a microbial insecticide for use against many major pests, including lepidopterans and orthopterans.…”
Section: Introductionmentioning
confidence: 99%
“…Different study reported that EPF isolates can serve pest control for long period of time without affecting the natural enemies while; the chemical control is for short period of time for as soon as the pest can develop resistance against it [51]. Mensah & Young, and Bayu & Prayogo also reported that use of B. bassiana is safe to the predators and effectively increased the yield as compared with the application of chemical insecticide on mungbean insect pest and Bemisia tabaci on cotton crop, respectively [54,55]. This indicates that PPRC-44BC and PPRC-27J isolates are good candidates for further study against antestia bug.…”
Section: Discussionmentioning
confidence: 99%
“…Alonso-Dı´az et al [30] also reported that repeated treatment of Ma34 strain controlled the natural infestation of engorged female Boophilus microplus on cattle in the Mexican tropics. Even though there is a limitation of literatures on antestia bug, different authors [30,31] reported on other pests that application of B. bassiana four to six times can suppress the population of Empoasca sp., Riptortus linearis, and Maruca testulalis, but did not significantly differ when compared with the application of chemical insecticides. Application of B. bassiana six times led to significantly high yield (659.7 g/plot) as compared with the application of chemical insecticide (374 g/plot) [31].…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is a limitation of literatures on antestia bug, different authors [30,31] reported on other pests that application of B. bassiana four to six times can suppress the population of Empoasca sp., Riptortus linearis, and Maruca testulalis, but did not significantly differ when compared with the application of chemical insecticides. Application of B. bassiana six times led to significantly high yield (659.7 g/plot) as compared with the application of chemical insecticide (374 g/plot) [31]. Additionally, the time required to reach complete mortality of the pest also decreased with increasing exposure time [32,33].…”
Section: Discussionmentioning
confidence: 99%